How do formal caregivers experience the sexuality of older adults? Beliefs and attitudes towards older adults’ sexuality - Monteiro, Ana (2018)
Aim: The way caregivers experience the sexuality of older adults has implications to their identity and sexual manifestations. There are few studies that focus on the meaning of caring of older adults, taking into account their sexuality. This study aims to explore the experiences of formal caregivers (FC) towards sexuality among older adults, and to obtain a description of their experiences. Method: Complete data were available from six caregivers working in a nursing home. We used a sociodemographic questionnaire and topic interview guide. The data was subjected to content analysis. Results: The most prevalent response of the interviewed participants for ‘beliefs about the interest in sexuality’ was ‘health limitations despite the desire’, for ‘observed behaviours related to sexual expression’ was ‘masturbation’, and for ‘reactions/behaviours due to the demonstration of sexual expression was ‘using humour”. Conclusion: Future educational and intervention programs in the institution should take into account our findings to improve their efficacy on discussing these issues and to ultimately promote sexual wellbeing.